Impact of immobilization system angle, body mass index and breast size on breast radiotherapy accuracy using EPID-only setup - Ioana-Claudia Costin; Loredana G. Marcu (Heliyon)
This study aims to assess setup errors for patients immobilized on different board inclinations and to evaluate the effect of body mass index (BMI) and breast size on positioning errors. Furthermore, the dosimetric impact of setup errors on target and organs at risk was measured using three different irradiation techniques (3D conformal radiotherapy, intensity modulated and volumetric modulated arc radiotherapy). A cohort of 40 breast cancer patients was split into two groups as a function of immobilization board inclination: 20 patients immobilized on 7.5° inclination (group A) and 20 on 0° (group B). Systematic and random errors were determined with weekly portal and tangential images. A strong correlation between BMI and both systematic (r = 0.720) and random errors (r = 0.752) was observed in posterior direction for group B, while the correlation between breast size and setup errors showed a moderate association under systematic errors for right (r = −0.507) and left (r = 0.503) directions. The dosimetric impact of setup errors on target volume showed higher contribution from systematic than from random errors. Suboptimal coverage of target volume was more prominent in group A for all planning techniques (46.65Gy 3DCRT, 46.95Gy IMRT, 46.90Gy VMAT). Patients with high BMI could benefit from the inclined immobilization board with a higher frequency of image position verification. When comparing 3DCRT versus modulated techniques the ipsilateral lung is better spared with the latter, while the contralateral lung is more efficiently protected with conformal technique.